Distinct pleiotropic effects of direct oral anticoagulants on cultured endothelial cells: a comprehensive review - Atzemian, Natalia; Kareli, Dimitra; Ragia, Georgia; Manolopoulos, Vangelis G. (Frontiers in Pharmacology, 2023)
Direct Oral Anticoagulants (DOACs) have simplified the treatment of thromboembolic disease. In addition to their established anticoagulant effects, there are indications from clinical and preclinical studies that DOACs exhibit also non-anticoagulant actions, such as anti-inflammatory and antioxidant actions, advocating overall cardiovascular protection. In the present study, we provide a comprehensive overview of the existing knowledge on the pleiotropic effects of DOACs on endothelial cells (ECs) in vitro and their underlying mechanisms, while also identifying potential differences among DOACs. DOACs exhibit pleiotropic actions on ECs, such as anti-inflammatory, anti-atherosclerotic, and anti-fibrotic effects, as well as preservation of endothelial integrity. These effects appear to be mediated through inhibition of the proteinase-activated receptor (PAR) signaling pathway. Furthermore, we discuss the potential differences among the four drugs in this class. Further research is needed to fully understand the pleiotropic effects of DOACs on ECs, their underlying mechanisms, as well as the heterogeneity between various DOACs. Such studies can pave the way for identifying biomarkers that can help personalize pharmacotherapy with this valuable class of drugs.